The diverse and widespread Southern Ocean ophiuroid Amphiura belgicae should be considered a species complex - Sands, Chester J.; Goodall-Copestake, William P.; Stöhr, Sabine; Narayanaswamy, Bhavani E.; Convey, Peter; O’Hara, Timothy D.; Martín-Ledo, Rafael (Frontiers in Ecology and Evolution, 2024)
Accurate knowledge of geographic ranges of species is essential for effective conservation management. Species with large distributions and good connectivity are presumed to be resilient to adverse localized/regional conditions, whereas those with small ranges and, thus, smaller population sizes are more likely to be vulnerable. The rich benthic assemblages across the Southern Ocean are generally considered “Antarctic” with some input from South America contributing to diversity on the sub-Antarctic island shelves. However, molecular work over the past two decades is challenging the paradigm of a general Antarctic benthic fauna, with evidence mounting for assemblages being regionally unique in terms of genetic diversity, regardless of formal taxonomic species composition. The widely distributed brittle star, Amphiura belgicae, is one element of the Southern Ocean benthic assemblage that has a complex historical taxonomic background hinting that it may in reality be a complex of species, each with small geographic range and little connectivity. Our study identified deep genetic divisions between geographically isolated populations, particularly between those on the Patagonian shelf and elsewhere. Indeed, populations on the Patagonian shelf were more closely related to the sympatric sister species A. eugeniae than to any other Southern Ocean population. We compare our data with a study of Ophiuroglypha lymani from similar collections, highlighting that both show highly regionalized populations, particularly on Island shelves, and both share the curious phenomenon of a presumed outgroup species being an element of the ingroup. We suggest that the isolated populations of both these species are following distinct evolutionary and ecological trajectories and that both should be treated as species complexes.